Penyelesaian Perselisihan Pembatalan Kontrak Pertunjukan Musik Akibat Efek Tindakan Kontroversial - Tarigan, Gita Gisela Andriani Br; Sukarja, Detania; Harianto, Dedi; Azwar, Tengku Keizerina Devi (Fakultas Hukum, Universitas Muslim Indonesia, 2024)
This research aims to analyze the category of music performance contract cancellations due to controversial actions and the forms of non-litigation dispute resolution between the event organizer and 1975. This study combines normative and empirical research methods. Subsequently, the collected data were analyzed qualitatively to describe the problem and address the research purposes. The results show that the controversial actions of The 1975 vocalist in Malaysia, leading to the cancellation of their performance at “We the Fest 2023” in Jakarta, constitute a breach of contract. This cancellation not only reveals the direct impact on the event but also highlights the importance of clauses in contracts that specifically regulate public behavior and the potential consequences of such behavior, both legally and ethically. Furthermore, the dispute resolution between the Event Organizer and The 1975 following the cancellation of their performance was achieved through negotiation. The dispute resolution process between the two parties was effective and took only two days, demonstrating that negotiation is a quick and efficient non-litigious method. Therefore, it is recommended that event organizers and artists, singers, or bands include and clarify clauses in performance contracts related to public behavior and its potential consequences. These clauses should detail the fines or legal consequences that may arise from controversial actions that could negatively affect the execution of the contract or the reputation of the involved parties. Additionally, Event Organizers are advised to set behavior standards that band personnel must adhere to while on stage, thereby minimizing the risk of future music performance cancellations. Lastly, both Event Organizers and music bands should prioritize non-litigation as the initial step before pursuing litigation, as negotiation has proven efficient and effective in resolving disputes arising from breaches of contract due to controversial actions.